FRI0157 OBSERVATIONAL STUDY OF HAIR FALL IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH LOW DOSE METHOTREXATE COMPARED TO HEALTHY CONTROLS. (June 2019) - Kumar, Sharath; Lokanath, Dhivya
Abstract : Background: Chemotherapeutic drugs are known to cause of hair loss(typically anagen effluvium, starts at 2-4 weeks and most apparent at 1-2 months).(1) The effect of hair fall (or the perceived possibility of it) can be so distressing that up to 8% of patients may choose less effective chemotherapy regimens that do not cause hair loss.(2) Low dose methotrexate used in rheumatology has a different mode of action and side effect profile compared to methotrexate at doses used in oncology.(3) Hence this study aimed to clarify whether low dose methotrexate carried a risk of hair fall. Objectives: Determine the mean change in number of hair strands obtained by the hair pull test at the start of the trial and at 3 weeks, 2 months and 3 months among rheumatoid arthritis patients on methotrexate in comparison to healthy controls. Methods: After ethics commitee approval and informed consent, consecutive patients attending a rheumatology OPD and who were planned to be initiated on methotrexate were enrolled into the study. Patient relatives, hospital staff and healthy blood donors were recruited as healthy controls. Patients with prior exposure to methotrexate in the last 6 months, currently on other medications known to cause hair fall or those suffering from diseases which could predispose to alopecia were excluded. Results: During the 6 month enrollement phase 98 patients and 82 controls were enrolled. Patients were 85% female with a mean age of 48.1+13.4. Rheumatoid factor positivity was seen in 56%. Average duration of the disease was 9.6 months (Range 15 days to 3 years) Pateints were started on 10 to 15 mg of methotrexate which was escalted at the 1st visit at 3 weeks. Only 3 patients had received prior DMARDs. Controls also constitued predominatly women (90%) with an slightly lower average age of 44.4 +10.9 years. The mean no of hair in the hair pull test at the start of the study was 1.21+2.01 (range 0-12) in pateints vs 0.84+1.25 (range0-4)in controls. The mean change in the hair count in the same test repeated at 3 weeks, 2 months and 3 months was -0.29, -0.31 & -0.26 respectively.(i.e. reduction in hair fall). In comparison healthy controls showed values of 0.31, 0.11, 0.1 at the same follow up points. There was no statistical significant difference in the proportion of patients having more that 5 hairs in the test at the onset of treatment vs healthy controls or during any point during the follow up period Conclusion: Low dose methotrexate did not appear to predispose to increased hair fall during this short term study. In fact many patients showed reduction in the number of hair in the hair pull test on methotrexate References: [1] Tosti A, Pazzaglia M. "Drug reactions affecting hair: Diagnosis." Dermatol Clin 2007;25:223-31. [2] Malaviya AN, Sharma A, Agarwal D, Kapoor S, Garg S, Sawhney S. Low-dose and high-dose methotrexate are two different drugs in practical terms. International Journal of Rheumatic Diseases 2010; 13: 288–293. [3] Batchelor D.Hair and cancer chemotherapy: consequences and nursing care-a literature study.Eur J Cancer Care (Engl). 2001 Sep;10(3):147-63. Acknowledgement: Dr Deena Patil and Dr Sunaina Hameed for help in designing the study Disclosure of Interests: Sharath Kumar Consultant for: Intas, Speakers bureau: Janssen&Janssen, Bristol Meyers & Squibbs, Pfizer, Dhivya Lokanath: None declared